The cooperation between kindergartens and families during the closure of the kindergarten in Slovenia due to the COVID-19 pandemic - Mervic, Tina; Zgonec, Petra (Psihološka istraživanja, 2021)
During 2020, kindergartens in Slovenia were fully closed in the first and partially closed in the second wave of the COVID-19 pandemic. Therefore, the kindergarten practice of cooperation with the families changed. In order to obtain an insight into the new situation in this field, our research focused on the organization of the cooperation between kindergartens and families during the kindergarten closure. In November 2020, we developed an online questionnaire for parents who had at least one child enrolled in kindergarten. The questionnaire was filled in by 944 parents. More than half of the parents answered that contacts with preschool professionals had supported them during the full and/or partial closure of their kindergarten. About one half of parents answered that the kindergarten had contacted them once a week, mainly with proposals for activities and information in case the kindergarten remained closed. Most parents answered that the additional contact with the professionals had not represented an additional workload. Three quarters of parents believe that it is necessary to maintain contact even during the closure. Still, as the pandemic situation is completely new, it is still difficult to assess in what way it makes sense to maintain cooperation during the closure. With the study, we obtained insight into the importance of cooperation from the parents’ perspective, which we need to consider in similar situations ahead.
Keywords: COVID-19, kindergartens, parents, preschool children, collaboration